Stories spun in DNA: Unravelling the fine-scale genomics of ancient Scotland - McCann, Maeve Margaret (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2025)
The growing field of ancient genomics has revealed the broad genomic changes associated with major archaeological horizons in past Britain and Ireland. It has been established that genomic continuity exists between the Bronze Age and modern Scotland. However, there remain major gaps in the understanding of regional trends, which could be better understood with additional genetic sampling from ancient Scottish contexts and the application of haplotype-based techniques which have given fine-scale resolution on modern day populations. 50 individuals from Scotland dating from the Bronze Age to Medieval period were sequenced using shotgun sequencing, in an attempt to bring greater resolution on the regional geographic and temporal trends within the study area. Findings of a near-complete genetic turnover in both England and Scotland at the beginning of the Bronze Age were replicated using Identity-By-Descent (IBD) analysis. A composite skeleton in a Bell Beaker context was identified using molecular sexing of the petrous bone, revealing the individual was a male with high IBD connectivity to other early Bronze Age populations including Germany and Netherlands. An unidentified petrous from Late Bronze Age Cladh Hallan was found to be a human male with a signal of population isolation in his genome. In Late Iron Age-Early Medieval Shetland we find three separate ancestries from three different individuals, two of whom are third degree relatives. We characterise the earliest sample as an insular Pict with localised Iron Age ancestry and a strong signal of an isolated population. We identify an early Christian burial with predominantly Anglo-Saxon-like ancestry and his later third degree relative who has a different genetic profile, including connections to the Viking world. In the Later Medieval east coast burghs of Aberdeen and Perth we document a cosmopolitan group with varied ancestry and connections across both Britain and Europe, indicative of distant trade and urban development. We find a significant increase in IBD sharing with English populations through time in this cohort which we interpret as the beginning of the genetic differences between modern day west and east Scotland. Finally we reveal that a murdered child from Medieval Perth is a young girl. These newly generated samples, combined with existing data and the power of haplotype approaches reveal hitherto unknown connections within and to Scotland, providing a greater resolution on past societies and the foundation of modern day genetic structure.
APPROVED
Keywords: ancient DNA; archaeogenomics; Scotland; Medieval; population genetics; Genetics; Anthropology; Archaeology